Development of an RME-Based E-Module to Improve Junior High School Students’ Conceptual Understanding and Statistical Problem-Solving Skills - Ratna Wati Seri Jala; Christina Ismaniati (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Low mathematical conceptual understanding and problem-solving ability remain significant challenges in statistics learning at SMP Negeri 4 Waibakul. Teacher-centered instruction and the limited availability of contextual teaching materials and digital learning resources have reduced students’ engagement in the learning process. This study aimed to develop a Realistic Mathematics Education (RME)-based e-module that is feasible, practical, and effective in improving students’ conceptual understanding and mathematical problem-solving skills. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The participants consisted of 39 seventh-grade students selected through purposive sampling. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The findings revealed that the developed e-module met the criteria of being highly feasible and highly practical. The effectiveness of the e-module was indicated by N-Gain scores of 0.77 for conceptual understanding and 0.80 for problem-solving ability, both categorized as high. In addition, there was a significant difference between the experimental and control groups. These findings demonstrate that the RME-based e-module effectively supports contextual mathematics learning, particularly in improving students’ conceptual understanding and problem-solving skills simultaneously.